REPRODUCTIVE BIOLOGY OF LONGTAIL TUNA (Thunnus tonggol) IN THE JAVA SEA - Thomas Hidayat; Mennofatria Boer; Mohammad Mukhlis Kamal; Zairion Zairion; Ali Suman (Indonesian Fisheries Research Journal, 2020)
Longtail tuna (Thunnus tonggol) is one of common economically important pelagic fish species in Indonesia. The objective of this study is examining the biology of reproduction, consisting of length of weight relationship, sex ratio, maturity stage, gonado somatic index (GSI), length at first capture, and length at first maturity and spawning pattern. A total of 633 longtail tuna, ranging 29-58 cmFL and consisting of 293 males and 340 females, were collected from the Java Sea between April 2018 and March 2019. The results showed that the longtail tuna growth pattern was isometric. The sex ratio was not significantly different between male and female. The length of first capture longtail tuna of drift gillnet (43.2 cmFL) was bigger than the length at first maturity (42,3 cmFL). This indicates that the most of longtail tuna caught by drift gillnet have already spawned. The peak’s spawning season occurred in May and November, with fecundity ranging from 783,597 - 1,579,160 eggs. Longtail tuna has multiple spawning pattern